Perancangan Desain Kemasan Produk Basreng pada UMKM Kusukangemil Menggunakan Metode Kansei Engineering - I Made Yudi Mertha Antara; I Gusti Agung Kade Suriadi; Ni Luh Putu Lilis Sinta Setiawati (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
UMKM Kusukangemil is one of the UMKMs that sells basreng products in Denpasar. Currently, the packaging design for the basreng products used is quite simple, making it difficult for the product to compete in the market. To increase competitiveness, a redesign of the product packaging is required to make it more attractive and innovative. This study aims to determine consumer preferences for basreng product packaging using the Kansei Engineering method, and to design the basreng product packaging based on these consumer preferences. The Kansei Engineering method is used in this study because it can interpret consumers' emotional responses and needs toward a product or concept. Through this approach, Kansei Words were collected through a questionnaire given to 50 respondents. These words were then analyzed to determine the most desired design elements by consumers. The results of the study indicate that consumers want basreng product packaging to be colorful, made of food-grade material, include expiration date and composition information, BPOM certification, be vertical in shape, made of thick material, be in the form of a bag, have motifs, halal certification, include address and social media information, and use bold fonts. Based on these results, two packaging design concepts were developed and selected based on consumer preferences. The resulting packaging design is expected to increase the attractiveness of UMKM Kusukangemil’s basreng products, making them more competitive in the market. Additionally, good packaging design is also expected to represent a quality product image and increase sales.